Analysis of The Teacher's Role in The Implementation and Development of The Al-Qur'an Tahfiz Curriculum in Islamic Boarding Schools - Tusholihat, Murtaqia; Ali, Mohammad; Hernawan, Asep Herry; Dewi, Laksmi (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to formulate learning objectives, strategies in achieving memorization targets, how to carry out the Al-Qur'an tahfiz learning curriculum. The research method used is a qualitative approach by directly analyzing the daily activities of teachers and participants through various processes including muayasyah, research and development, interview, library, and documentation. This research was conducted in five Islamic boarding schools in West Java, Indonesia. The results of the research show that teachers are at the forefront of curriculum development, that every teacher must be smart in capturing every situation that develops. The results of research on Islamic boarding schools show that by giving teachers the widest possible authority to carry out the curriculum and develop it according to situations and conditions in the field, it has succeeded in facilitating students to achieve memorization targets according to their respective abilities. That the materials and learning strategies that have been developed can be used as comparisons in order to improve teacher quality. From this study it can be concluded that in the work of compiling the curriculum it is not enough to only use experts but also must involve experienced teachers as a team and contributors of ideas from the field.